Intrinsic Chirality Origination in Carbon Nanotubes - Pierce, Neal; Chen, Gugang; P. Rajukumar, Lakshmy; Chou, Nam Hawn; Koh, Ai Leen; Sinclair, Robert; Maruyama, Shigeo; Terrones, Mauricio; Harutyunyan, Avetik R (ACS nano, 2017)
Elucidating the origin of carbon nanotube chirality is key for realizing their untapped potential. Currently, prevalent theories suggest that catalyst structure originates chirality via an epitaxial relationship. Here we studied chirality abundances of carbon nanotubes grown on floating liquid Ga droplets, which excludes the influence of catalyst features, and compared them with abundances grown on solid Ru nanoparticles. Results of growth on liquid droplets bolsters the intrinsic preference of carbon nuclei toward certain chiralities. Specifically, the abundance of the (11,1)/χ = 4.31° tube can reach up to 95% relative to (9,4)/χ = 17.48°, although they have exactly the same diameter, (9.156 Å). However, the comparative abundances for the pair, (19,3)/χ = 7.2° and (17,6)/χ = 14.5°, with bigger diameter, (16.405 Å), fluctuate depending on synthesis temperature. The abundances of the same pairs of tubes grown on floating solid polyhedral Ru nanoparticles show completely different trends. Analysis of abundances in relation to nucleation probability, represented by a product of the Zeldovich factor and the deviation interval of a growing nuclei from equilibrium critical size, explain the findings. We suggest that the chirality in the nanotube in general is a result of interplay between intrinsic preference of carbon cluster and induction by catalyst structure. This finding can help to build the comprehensive theory of nanotube growth and offers a prospect for chirality-preferential synthesis of carbon nanotubes by the exploitation of liquid catalyst droplets.